Protective factors against bullying and cyberbullying: A systematic review of meta-analyses - Zych, Izabela; Farrington, David P.; Ttofi, Maria M. (Aggression and violent behavior, 2019)
Bullying and cyberbullying are damaging aggressive behaviors in which some children and adolescents intentionally inflict frequent and long term harm on peers who become victimized. The number of studies on bullying is high and a lot of knowledge has already been gathered. Nevertheless, there are still many gaps in knowledge that need to be addressed. Research on protective factors and effective interventions is still in its relatively early stages. This systematic review of meta-analyses on protective factors against bullying and cyberbullying was conducted to synthesize knowledge and discover the most important community, school, family, peer and individual protective factors. After systematic searches and the application of inclusion and exclusion criteria, 18 meta-analyses with 128 effect sizes were included and analyzed. Forest plots were constructed and median effect sizes were calculated for each group of protective factors. Self-oriented personal competencies were the strongest protector against victimization. Low frequency of technology use protected from involvement in cyberbullying. Good academic performance and other-oriented social competencies were the strongest protective factors against perpetration. Positive peer interaction was the strongest protective factor against being a bully/victim. These findings can be useful to improve anti-bullying programs, policy and practice. •Bullying and cyberbullying are very damaging aggressive behaviors present in schools.•A systematic review of meta-analyses on protective factors against bullying and cyberbullying was conducted.•Forest plots were constructed and median effect sizes were calculated for different protective factors based on 128 overall effect sizes.•Community, school, family, peer and individual protective factors against bullying and cyberbullying were found.•Findings are useful to improve anti-bullying programs, policy, and practice.